Validation of the Motivated Strategies for Learning Questionnaire among clinical clerkship students in Malaysia - Sahar Fatima; Vinod Pallath; Wei-Han Hong (PLoS ONE, 2025)
The 81-item Motivated Strategies for Learning Questionnaire (MSLQ) is a validated tool for measuring self-regulated learning (SRL) and comprises two scales, Motivation and Learning strategies. Although its use in health professions education has been well established, validation in clinical clerkship years is scant. This study aims to investigate the structural validity and internal consistency of MSLQ in the context of Malaysian clinical clerkship students. The data from 349 clinical clerkship students, who completed the adapted MSLQ was used to test the internal consistency and hypothesised factor structure using confirmatory factor analysis for both the Motivation and Learning strategies scales. For the Motivation scale, the Cronbach’s alpha values ranged from 0.63 to 0.90 and for the Learning strategies scale from 0.61 to 0.86, indicating acceptable to high internal consistency. Cronbach’s alpha for whole MSLQ was 0.91, suggesting an excellent reliability of MSLQ in our sample. The model fit indices for the Motivation scale were comparable to the original MSLQ indicating a reasonable fit whereas the model fit indices for the Learning strategies scale did not fit well with our sample and required re-specification to attain a marginal fit. After re-specification for a better model fit, the six-factor Motivational scale and nine-factor Learning strategies scale retained their original constructs in our population sample of clinical clerkship students. Comparing our findings with the original MSLQ and previous studies, we can claim a marginal fit of our data and the theoretical model and suggest the need for further testing with a larger sample size and across different institutions. We recommend that the 75-item re-specified MSLQ-CL could be valuable for future SRL investigations among clinical clerkship students in general as well as in context of Asian medical education context.